Job competition and entry wages of highly educated workers: are there differences between Great Britain and Finland? - Sanna-Mari Hynninen; Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper analyses the impact that local labour market conditions have on entry wages of highly educated workers in Great Britain and Finland. In both countries, workers entering the labour market in regions with (or periods of) tighter job competition obtain lower wages. Competition from employed job seekers has a negative impact on entry wages in both countries, while competition from unemployed job seekers has a negative impact only in Finland. Overall, the wage elasticity is larger in Great Britain than in Finland, suggesting that centralised collective bargaining might mitigate the impact that local labour market conditions have on entry wages.
Keywords: 330